Novel spectroscopic biomarkers are applicable in non-invasive early detection and staging classification of colorectal cancer - Miskovicova, M; Fryba, V; Petruzelka, L; Setnicka, V; Synytsya, A; Tatarkovic, M; Ulrych, J; Vocka, M (Neoplasma, 2020)
Colorectal cancer (CRC) remains a signiﬁcant threat to human health because of the lack of awareness of physical examination or the limitations of an early diagnostic level. Despite the improving standard of modern medicine, mortality from CRC is still remarkably high and the prognosis remains poor in many cases because of disease detection at advanced clinical stages. Raman spectroscopy yields precise information, not only regarding the secondary structure of proteins but also regarding the discrimination between normal and malignant tissues. We investigated whether this method can be used for the diagnosis of CRC including initial stages. To acquire more detailed structural information, we tested a novel diagnostic approach based on a suitable combination of conventional methods of molecular spectroscopy (Raman and Fourier transform infrared) with advanced, highly structure-sensitive chiroptical techniques as electronic circular dichroism (ECD) and Raman optical activity (ROA) to monitor the CRC pathogenesis relating compositional, structural and conformational changes in blood biomolecules, some of which may be caused by pathological processes occurring during cancer growth, also at the beginning of the disease. Sixty-three blood plasma samples were analyzed using the combination of ECD and ROA supplemented by Raman and Fourier transform infrared (FT-IR) spectroscopies. The obtained spectra were evaluated together by linear discriminant analysis. The accuracy of sample discrimination reached 100% and the subsequent leave-one-out cross-validation resulted in 90% sensitivity and 75% specificity. There were also found the differences between the patients according to the clinical stage. The achieved results suggest a panel of promising biomarkers and indicate that chiroptical methods combined with conventional spectroscopies might be a new minimally invasive powerful tool for producing high-quality data, obtaining an accurate diagnosis of colorectal cancer through a peripheral blood sample, which is also able to determine the extent of this pathology. Further work needs to be carried out for these techniques to be implemented in the clinical setting.
Keywords: Early Detection of Cancer; Neoplasm Staging; Colorectal Neoplasms; staging nádorů; Spectroscopy, Fourier Transform Infrared; nádorové biomarkery; cirkulární dichroismus; Spectrum Analysis, Raman; Humans; spektroskopie infračervená s Fourierovou transformací; Circular Dichroism; kolorektální nádory; Ramanova spektroskopie; lidé; časná detekce nádoru; Biomarkers, Tumor